Social capital and rural development: literature review and current state of the art; Sozialkapital und ländliche Entwicklung: Literaturüberblick und gegenwärtiger Stand der Forschung - Thomas Dufhues; Gertrud Buchenrieder; Isabel Fischer (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2006)
Social capital has been recently held up as a conceptual framework to build a bridge between the diverse disciplines involved in rural development. However, despite its potential and the impressively rapid take-up of the concept by the community of development professionals, it remains an elusive construct. No definition is yet generally accepted and many definitions are in use. Recently, social capital in the form of social networks has gained much attention in rural development theory and empirical research. But social networks or structural components of social capital are a largely missing dimension in income and poverty analysis. Moreover, most research on social capital assumes that it is a uniform entity. Therefore, the effects of different forms of social capital on household outcome are rarely investigated. The objective of this discussion paper is to make the concept of social capital more tangible for empirical research in the area of rural development and to bring more structure into the conceptual framework of social capital. On the basis of an extensive literature review, this work proposes a lean and clear definition of social capital: Social capital is conceived as networks plus resources, (e.g. credit, information). Moreover, social capital is assumed to be not a homogeneous entity. Hence, it is necessary to distinguish different forms of social capital. For analytical purposes, the separation into so-called bonding and bridging capital seems to be most appealing. These two forms of social capital can be operationalized as function of an agent's so-called weak ties (e.g. acquaintances) and so-called strong ties (e.g. close relatives). – – Sozialkapital hat innerhalb der letzten zwei Jahrzehnte als interdisziplinäres Konzept eine enorme Bedeutung sowohl in der Wissenschaft als auch in der praktischen ländlichen Entwicklung erlangt. Trotz eines 'Booms' an wissenschaftlichen und nicht wissenschaftlichen Arbeiten bleibt das Konzept wenig greifbar. Bisher konnte sich die wissenschaftliche Gemeinde auf keine allgemeingültige Definition einigen. Sehr unterschiedliche und zum Teil sehr umfassende Definitionen sind in Gebrauch. Neuere Arbeiten tendieren allerdings dazu, Sozialkapital enger zu definieren und Netzwerke in den Vordergrund zu stellen. Nichtsdestotrotz werden strukturelle Komponenten von Sozialkapital oder Netzwerken nur selten in Einkommens- und Armutsanalysen einbezogen. Es wird auch noch oft unterstellt, dass Sozialkapital eine homogene Ressource ist. Deshalb werden dessen unterschiedlichen Ausprägungen noch seltener untersucht. Das Hauptziel dieses Diskussionspapiers ist es, einen geeigneten Ansatz für die empirische Forschung im Bereich ländlicher Entwicklung, basierend auf dem Netzwerkansatz, herauszuarbeiten. Basierend auf einer intensiven Literaturrecherche empfiehlt das Papier eine klare und einfache Definition von Sozialkapital. Sozialkapital wird als Netzwerk plus Ressourcen definiert. Unterschiedliche Formen von Sozialkapital ('Bonding' und 'Bridging') werden über die Stärke der Beziehung der Netzwerkteilnehmer bestimmt.
urn:nbn:de:gbv:3:2-1505
Keywords: D85; Z13; 330; Social capital; individual social capital; measuring social capital; ego-network; social networks